Study of Flood Disaster Risk Delta in Bojonegoro Regency - Widodo, Widiyanto Hari Subagyo; Imadudinna, Annisa Hammidah; Sasongko, Ibnu (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2022)
A disaster is an unexpected and often sudden event that causes destruction, serious damage, and human suffering. According to the Law of the Republic of Indonesia Number 24 of 2007 concerning Disaster Management, disasters are caused by natural factors and/or non-natural and human factors so that disasters can result in loss of life, environmental damage, loss of property, and psychological impacts. Bojonegoro Regency which has the widest area crossed by the Bengawan Solo river and 24,753 hectares of its area is a watershed so that almost every year Bojonegoro Regency is flooded when the Bengawan Solo river overflows. Floods in Bojonegoro Regency almost occur every year. Where the flood that occurred in Bojonegoro Regency was caused by the overflow of the Bengawan Solo river. As much as 63% of the total population of Bojonegoro Regency is exposed or at risk of flooding in 2012 to 2020. This study is to determine the Delta (Δ) risk of flood-prone areas in Bojonegoro Regency based on trends in land use change with a multitemporal perspective in Bojonegoro Regency. This study uses the latest methods, especially in terms of spatial modeling, namely TIN and Raster databases. The first step is to predict the trend of land use in Bojonegoro Regency. Which is then continued to identify flood hazards and land use vulnerabilities. Flood disaster-prone areas each year are predicted based on the previous stages using the Analytic hierarchy process which then produces disaster risk in each prediction year. The last step is to calculate the amount of change or Delta (∆) of Flood Disaster Risk in Bojonegoro Regency. The results of this study are Delta (∆) Low Flood Disaster Risk: experienced a change of -1.62% or decreased by 49.66 Ha from 2020 to 2040. Delta (∆) Moderate Flood Disaster Risk: experienced a change of 2.85% or experienced an increase of 17.67 Ha from 2020 to 2040. Delta (∆) High Flood Risk: experienced a change of 23.96% or an increase of 31.99 Ha from 2020 to 2040.